Engaging dystonia networks with subthalamic stimulation - Konstantin Butenko; Clemens Neudorfer; Till A. Dembek; Barbara Hollunder; Garance M. Meyer; Ningfei Li; Simón Oxenford; Bahne H. Bahners; Bassam Al-Fatly; Roxanne Lofredi; Evan M. Gordon; Nico U. F. Dosenbach; et al. (Proceedings of the National Academy of Sciences, 2025)
Deep brain stimulation is an efficacious treatment for dystonia. While the internal pallidum serves as the primary target, recently, stimulation of the subthalamic nucleus (STN) has been investigated. However, optimal targeting within this structure and its surroundings have not been studied in depth. Indeed, historical targets that have been used for surgical treatment of dystonia are directly adjacent to the STN. Further, multiple types of dystonia exist, and outcomes are variable, suggesting that not all types would profit maximally from the same target. Therefore, a thorough investigation of neural substrates underlying stimulation effects on dystonia signs and symptoms is warranted. Here, we analyze a multicenter cohort of isolated dystonia patients with subthalamic implantations ( N = 58) and relate their stimulation sites to improvements of appendicular and cervical symptoms as well as blepharospasm. Stimulation of the ventral oral posterior nucleus of thalamus and surrounding regions were associated with improvements in cervical dystonia, while stimulation of the dorsolateral STN was associated with improvements in limb dystonia and blepharospasm. This dissociation was matched by structural connectivity analysis, where the cerebellothalamic, corticospinal, and pallidosubthalamic tracts were associated with improvements of cervical dystonia, while hyperdirect and subthalamopallidal pathways with alleviation of limb dystonia and blepharospasm. On the level of functional networks, improvements of limb dystonia were associated with connectivity to the corresponding somatotopic regions in the primary motor cortex, while alleviation of cervical dystonia to the cingulo-opercular network. These findings shed light on the pathophysiology of dystonia and may guide DBS targeting and programming in the future.